Parenting Style dan Kesejahteraan Psikologis pada Remaja Penyandang Disabilitas Fisik - Nathan, Felicia Christofani; Huwae, Arthur (Personifikasi: Jurnal Ilmu Psikologi, 2024)
Parenting patterns are one of the challenges and can also be risky in the lives of children including adolescents with physical disabilities if the patterns applied are not appropriate. This will greatly impact the process of achieving psychological well-being in the daily lives of adolescents with disabilities. For this reason, this study aims to determine the relationship between parenting style and psychological well-being in adolescents with physical disabilities. The method used is quantitative with cross-sectional correlation analysis. The participants in this study were 109 adolescents with physical disabilities. Research measurements used Ryff's Psychological Well-Being Scale (RPWBS) and Parenting Styles and Dimensions Questionnaire (PSDQ). The results prove a significant positive relationship between authoritative parenting style and psychological well-being (r = 0.564 and sig. = 0.000). There is a significant negative relationship between authoritarian parenting style and psychological well-being (r = -0.587 and sig. = 0.000). There is a significant negative relationship between permissive parenting style and psychological well-being (r = -0.557 and sig. = 0.000). The application of appropriate parenting patterns from parents will greatly help adolescents with physical disabilities face various challenges and tough situations in their daily lives.